Fundamentals of Entrepreneurship (ENT300) : Chobit Boutique / Hazra Afira Marzuki … [et al.] - Marzuki, Hazra Afira; Apon, Loviana Mei; Abdul Rahman, Mohd Shafiq; Abdul Ghani, Nurhafieza; Zaidi 2016434602, Zarith Tihani Nabihah (2018)
hobit Boutique has been recognized by a certain amount of students in both campus in UiTM Kota Samarahan 1 and 2 and also UNIMAS especially female students. This is due to the location of the boutique is near to the They are selling clothes, various types of scarf, shoes, lipstick and other things. The main problem faced by Chobit Boutique is the competition with other boutiques that is also near to the UiTM and due to this problem, their sales drop and the economic problem such as the price of goods increasing. This problem is closely related to the economic problem. The other competitor likes to make sales and the customer will compare the prices.